2012
DOI: 10.1001/archdermatol.2012.2480
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Patient Performance of Skin Self-examinations After Intervention With Interactive Education and Telecommunication Reminders

Abstract: Objective:To determine if interactive computerized patient education, skin self-examination (SSE) tutorials, and telecommunication reminders could be combined to increase patient performance of SSEs, increase confidence in ability to identify melanoma, and influence individual melanoma risk perception.Design: A total of 132 adult participants from our dermatology clinics were enrolled in an interventional study and randomized to a control group or an intervention group. Survey data were collected from all part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
0
20
1
1
Order By: Relevance
“…The quality assessment of included RCTs showed that for items related to potential risk of bias due to allocation, nine of 12 RCTs provided a description indicating that the sequence was adequately generated and that the allocation was adequately concealed, and three studies [] had unclear descriptions of these processes. Blinding of participants, personnel and outcome assessors was reported as present in five studies [], not adequately described in three [], and four explicitly described their study was not blinded []. Incomplete outcome data were adequately described in two studies , unclearly described in nine studies [] and not adequately described to judge risk of bias in one study [].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality assessment of included RCTs showed that for items related to potential risk of bias due to allocation, nine of 12 RCTs provided a description indicating that the sequence was adequately generated and that the allocation was adequately concealed, and three studies [] had unclear descriptions of these processes. Blinding of participants, personnel and outcome assessors was reported as present in five studies [], not adequately described in three [], and four explicitly described their study was not blinded []. Incomplete outcome data were adequately described in two studies , unclearly described in nine studies [] and not adequately described to judge risk of bias in one study [].…”
Section: Resultsmentioning
confidence: 99%
“…Blinding of participants, personnel and outcome assessors was reported as present in five studies [], not adequately described in three [], and four explicitly described their study was not blinded []. Incomplete outcome data were adequately described in two studies , unclearly described in nine studies [] and not adequately described to judge risk of bias in one study []. For potential risk of bias from selective reporting, only one study [] indicated that a protocol was available by providing the trial registration number.…”
Section: Resultsmentioning
confidence: 99%
“…). From 22 included papers, detailed in Table S1 (see Supporting Information), we identified 18 included studies, as three papers reported on the same set of studies, with some reporting additional outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Secondary prevention research has addressed SSE behaviour to assist in early detection, using educational interventions, although knowledge may not be the only relevant behaviour‐related factor operating. Furthermore, many interventions employ digital technology strategies to facilitate the SSE process . However, there are no meta‐analyses of their effectiveness, and other than a single narrative review this is restricted to smartphone interventions .…”
mentioning
confidence: 99%
“…16,17 This form of communication may also be more cost-effective than telephone or print-based messaging. 14,18 Three studies have used SMS in the context of skin cancer prevention; [19][20][21][22] however, none evaluated in detail the user experience with such messages. The Healthy Text program included weekly to monthly text messages sent over 12 months.…”
Section: Introductionmentioning
confidence: 99%